The Effect of Morphometric Dimensions and River Drainage Network on the Hydrology of Tanjero River Basin in Sulaymaniyah Governorate - Zahraa Ahmed Fattah Naji; Dr. Suhaila Najem Al Ibrahimi (Migration Letters, 2023)
The study of the morphometric dimensions and the characteristics of the river drainage network in the basins is considered an important basis in the hydrological studies, as the natural environment factors and the local environment factors play a major role in drawing the engineering features of the water basins. Basically, it is based on data taken from topographical maps and others to determine the optimal use of the basin, which gives a clear vision of the possibility of exploiting and investing in the basin and explains the amount of water supply, the peak reaching the watercourse, the indication of flood risk and its length. Morphometric studies depend on the measurement and treatment of terrestrial features according to the basis of quantitative analysis by applying mathematical equations and statistical methods on data extracted from topographical maps, field measurements, aerial photographs and satellite visuals, in order to use their results in classifying terrestrial features and identifying the factors and processes that led to their emergence and development.